The Impact of Capital Structure and Macroeconomic Conditions on the Performance and Growth of Basic Material Companies on the Main Board of the Indonesia Stock Exchange (IDX) in the 2021-2024 Period - Dwi Danesty Deccasari Danesty; Marli (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of Capital Structure on Company Size with a focus on the role of leverage in driving operational scale expansion. The type of research used is quantitative research with SEM-PLS 4.0 analysis tools to test the relationship between Macro Fundamentals and Capital Structure on Financial Performance and Company Size. The research findings show that Macro Fundamentals have a significant positive influence on Financial Performance and Company Size. Capital Structure has a positive and significant influence on Company Size and Financial Performance, where increasing the proportion of debt as part of the capital structure effectively drives the growth of the company's production capacity, market, and workforce. The study emphasizes the importance of wise capital structure management as a key strategy in supporting long-term growth and maintaining company competitiveness in a competitive economic environment.